2015
DOI: 10.1111/ped.12651
|View full text |Cite
|
Sign up to set email alerts
|

Current incidence of clinical kernicterus in preterm infants in Japan

Abstract: Clinical kernicterus in preterm infants has recently been reported in Japan, diagnosed on the basis of clinical findings during the neonatal and infancy periods. We investigated the incidence of clinical kernicterus in preterm infants <30 weeks gestational age (GA) based on a nationwide survey conducted in 233 certified educational facilities for neonatologists. The numbers of infants admitted and infants who died within 14 days after birth during 2011, and the number of infants who subsequently developed clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 8 publications
(20 reference statements)
0
23
1
Order By: Relevance
“…(J Pediatr 2016;168:77-81).See editorial, p 6 C linical kernicterus has been observed in Japan, with an incidence of 1.8 per 1000 live births <30 weeks of gestational age (GA). 1 We previously found that total serum/plasma bilirubin (TB) levels in most very low birthweight (VLBW) infants with kernicterus peak after 1 week of age (median age: 28 days). 2 This finding indicates that VLBW infants should be continuously monitored for hyperbilirubinemia during their neonatal intensive care unit (NICU) stay, in contrast to monitoring for one week after birth as currently practiced in Japan.Transcutaneous bilirubin (TcB) measurements taken at the forehead and sternum are a noninvasive screening method for hyperbilirubinemia.…”
mentioning
confidence: 99%
“…(J Pediatr 2016;168:77-81).See editorial, p 6 C linical kernicterus has been observed in Japan, with an incidence of 1.8 per 1000 live births <30 weeks of gestational age (GA). 1 We previously found that total serum/plasma bilirubin (TB) levels in most very low birthweight (VLBW) infants with kernicterus peak after 1 week of age (median age: 28 days). 2 This finding indicates that VLBW infants should be continuously monitored for hyperbilirubinemia during their neonatal intensive care unit (NICU) stay, in contrast to monitoring for one week after birth as currently practiced in Japan.Transcutaneous bilirubin (TcB) measurements taken at the forehead and sternum are a noninvasive screening method for hyperbilirubinemia.…”
mentioning
confidence: 99%
“…9 To investigate the incidence, we conducted a nationwide survey targeting preterm infants <30 weeks of gestational age, who were born in 2011; five of 2,720 preterm infants included in the survey were diagnosed with chronic bilirubin encephalopathy. 12 Because chronic bilirubin encephalopathy in preterm infants is not fully recognized by neonatologists or pediatric neurologists, more undiagnosed cases may exist. Furthermore, chronic bilirubin encephalopathy was estimated to occur in at least 10 preterm infants per year in Japan in recent years.…”
Section: Chronic Bilirubin Encephalopathy In Preterm Newbornsmentioning
confidence: 99%
“…Sixty years have passed since phototherapy was invented to treat neonatal jaundice, but 0.4e2.7 per 100,000 newborn infants develop kernicterus. 1,2 The findings from several recent studies have shown that a sizeable fraction of verylow-birth-weight infants develop kernicterus caused by hyperbilirubinemia that occurs outside the typical high-risk period 3,4 ; hence, hyperbilirubinemia remains an important therapeutic target in newborn infants. Phototherapy reduces the total serum bilirubin (TSB) levels by accelerating the isomerization of serum bilirubin into cyclobilirubin, which is also known as lumirubin and photobilirubin II.…”
Section: Introductionmentioning
confidence: 99%